Understanding monsoon controls on the energy and mass balance of glaciers in the Central and Eastern Himalaya - S. Fugger; C. L. Fyffe; S. Fatichi; E. Miles; M. McCarthy; T. E. Shaw; B. Ding; W. Yang; P. Wagnon; W. Immerzeel; Q. Liu; F. Pellicciotti (The Cryosphere, 2022)
The Indian and East Asian summer monsoons shape the melt and accumulation patterns of glaciers in High Mountain Asia in complex ways due to the interaction of persistent cloud cover, large temperature ranges, high atmospheric water content and high precipitation rates. Glacier energy- and mass-balance modelling using in situ measurements offers insights into the ways in which surface processes are shaped by climatic regimes. In this study, we use a full energy- and mass-balance model and seven on-glacier automatic weather station datasets from different parts of the Central and Eastern Himalaya to investigate how monsoon conditions influence the glacier surface energy and mass balance. In particular, we look at how debris-covered and debris-free glaciers respond differently to monsoonal conditions. The radiation budget primarily controls the melt of clean-ice glaciers, but turbulent fluxes play an important role in modulating the melt energy on debris-covered glaciers. The sensible heat flux decreases during core monsoon, but the latent heat flux cools the surface due to evaporation of liquid water. This interplay of radiative and turbulent fluxes causes debris-covered glacier melt rates to stay almost constant through the different phases of the monsoon. Ice melt under thin debris, on the other hand, is amplified by both the dark surface and the turbulent fluxes, which intensify melt during monsoon through surface heating and condensation. Pre-monsoon snow cover can considerably delay melt onset and have a strong impact on the seasonal mass balance. Intermittent monsoon snow cover lowers the melt rates at high elevation. This work is fundamental to the understanding of the present and future Himalayan cryosphere and water budget, while informing and motivating further glacier- and catchment-scale research using process-based models.